Efficacy and Safety of Endovascular Therapy for Aortoiliac TASC D Lesions. (January 2017) - Suzuki, Kenji; Mizutani, Yukiko; Soga, Yoshimitsu; Iida, Osamu; Kawasaki, Daizo; Yamauchi, Yasutaka; Hirano, Keisuke; Koshida, Ryouji; Kamoi, Daisuke; Tazaki, Junichi; Higashitani, Michiaki; Shintani, Yoshiaki; et al.
Background: Although there is increasing evidence of the effectiveness of endovascular therapy for complex aortoiliac (AI) occlusive disease, it is not universally applied to TASC D lesions. Methods: A total of 2096 patients, 2601 limbs with AI occlusive disease, were enrolled. The lesions were categorized as TASC D (395) or TASC A-C (2206), and we compared baseline data, procedure, and follow-up result between the 2 groups. Results: The success rate of the procedure was significantly lower in the TASC D group (91.6% vs 99.3%, P < .01), and more procedure complications occurred in the TASC D group (11.1% vs 5.2%, P < .01). The results of a 5-year follow-up revealed no significant difference in primary patency (77.9% vs 77.1%, P = .17) and major adverse cardiovascular and limb events (MACLE; 30.5% vs 33.4%, P = .42) between the 2 groups. A multivariate analysis revealed complications and critical limb ischemia are independent predictors of MACLE in the TASC D group. Conclusion: The success rate of the procedure was lower in the TASC D group. Complications were more frequent in the TASC D group, and they were related to MACLE.